RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN PT CITRA MAHKOTA AMBAWANG - Amelia, Amelia; Diana, Tri; Noviryantika, Noviryantika (Jurnal Ekonomi Integra, 2025)
The purpose of this research is to assess the financial performance of PT. Citra Mahkota Ambawang during the 2022-2024. Period based  on  liquidity,  solvency, and  profitability  ratios.  The  population  of  this  research  is  the  annual  financial  report  of  PT. Citra Mahkota Ambawang  for  the  period  2022-2024.  The  sampling  technique  uses  a  non-probability  sampling  method  with  a saturated  sampling  approach,  namely  the  financial  report  of  PT. Citra Mahkota Ambawang which  includes  the  Balance  Sheet  and Profit and Loss Report for 2022-2024. This research is quantitative with a comparative analysis method using the Year-to-year Changes Analysis. The research results show that in terms of liquidity and solvency ratios the performance is quite than optimal because cash and cash equivalents have been able to fulfill all their obligations. From the profitability aspect, the company is able to generate profits and use assets efficiently based on GPM, NPM and ROI indicators.